O impacto da ambidestria na formação de capacidades não locais em subsidiárias de empresas multinacionais - Brunhara, Aldo José (2017)
The objective of this thesis was to verify the association of the Ambidexterity strategy with the formation of non-localized capacities (NLB-FSAs) in subsidiaries of Multinational Companies. The theoretical framework that underpinned the thesis was the resource-based view in international business and the OLI paradigm reflected in the discussion of the organizational capacities of foreign subsidiaries. The quantitative survey was conducted in April 2017 with foreign subsidiaries operating in Brazil. A total of 289 valid responses were received from various segments: industry, commerce and services. To test the model, multiple regression techniques were applied using the PLS (Partial Least Squares) system. The results confirm that Ambidexterity is associated with NLBFSA formation indirectly. Ambidexterity leads to local capacity building, in the form of LB-FSAs (Located Bound - Firm Specific Advantages). Subsidiaries with LB-FSAs present greater competitiveness, which in turn enables the subsidiary to transfer knowledge in the form of NLB-FSAs for the multinational's network. In theoretical terms, this research strengthens the RBV - Resource Based View and Dunning’s OLI theory (1980), more specifically, Ownership and Internalization, whereby through the ownership and exploitation of its resources abroad, MNEs develop and internalized capabilities, in the form of NLB-FSAs, from emerging markets. Regarding to the studies on Ambidexterity, the thesis shows that ambidextrous companies develop NLB-FSAs from the LB-FSAs capabilities that allow the improvement of Competitiveness. Additionally, it fulfills a gap in the studies on Ambidexterity since there are no studies on the impact of Ambidexterity on the formation of organizational capacities, LB-FSAs and NLB-FSAs in subsidiaries of multinational companies operating in Brazil. In terms of contribution to management, it supports in the definition of the strategic management model of multinationals, since, by using ambidextrous strategies, it enables the development of competitive organizational capacities from an emerging country.